2021
DOI: 10.1186/s40792-021-01252-1
|View full text |Cite
|
Sign up to set email alerts
|

CA19-9-producing esophageal adenocarcinoma originating from the esophageal cardia of the mid-thoracic esophagus: a case report

Abstract: Background Although there are many studies on primary esophageal adenocarcinoma arising from Barrett's esophagus or ectopic gastric mucosa, reports on adenocarcinoma arising from esophageal cardiac glands are extremely rare. Herein, we report a case of mid-thoracic cancer antigen 19-9 (CA 19-9)-producing primary esophageal adenocarcinoma, which presumably originated from the cardiac glands. Case presentation A 74-year-old man was referred to our de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…When EC cells proliferate and expand abnormally, CYFRA21-1 can be synthesized in large quantities and released into the blood by exocrine [ 28 ]. CA199 [ 29 ] is involved in the formation of tumor cells and can be released into the blood when tumor cells die, rupture, or proliferate, resulting in abnormal elevation of their serum level. Our results indicated that the levels of CEA, SCC, CYFRA21-1, and CA199 in the CRG group were lower than those in the RG group after treatment, indicating that synchronous chemoradiotherapy can promote the apoptosis of malignant tumor cells and suppress the generation of tumor-related factors compared with single chemoradiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…When EC cells proliferate and expand abnormally, CYFRA21-1 can be synthesized in large quantities and released into the blood by exocrine [ 28 ]. CA199 [ 29 ] is involved in the formation of tumor cells and can be released into the blood when tumor cells die, rupture, or proliferate, resulting in abnormal elevation of their serum level. Our results indicated that the levels of CEA, SCC, CYFRA21-1, and CA199 in the CRG group were lower than those in the RG group after treatment, indicating that synchronous chemoradiotherapy can promote the apoptosis of malignant tumor cells and suppress the generation of tumor-related factors compared with single chemoradiotherapy.…”
Section: Discussionmentioning
confidence: 99%